2017
DOI: 10.14716/ijtech.v8i5.865
|View full text |Cite
|
Sign up to set email alerts
|

Review of Facilities Management Functions in Value Management Practices

Abstract: This paper identifies the functions of facilities management (FM) in value management (VM) studies in Malaysia. Most previous research in this area has discussed the history, evolution, knowledge, challenges, and contributions of FM in both the private and the public sectors, yet it is also essential to explore the benefits of FM involvement and the drawbacks of FM noninvolvement in VM studies during the pre-construction stage in Malaysia. This paper provides an overview the FM manager's roles in a VM workshop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…They are also needed to prevent high capital costs, as well as the maintenance costs of green roofs (Ismail et al, 2016). As supported by Isa et al (2017), maintenance works must be prioritised and consider the building's current conditions and ease of access, as both influence related costs. Therefore, based on the analytical review of the literature, it was found that the results had a number of similarities with the maintenance criteria for green roofs found in previous studies.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…They are also needed to prevent high capital costs, as well as the maintenance costs of green roofs (Ismail et al, 2016). As supported by Isa et al (2017), maintenance works must be prioritised and consider the building's current conditions and ease of access, as both influence related costs. Therefore, based on the analytical review of the literature, it was found that the results had a number of similarities with the maintenance criteria for green roofs found in previous studies.…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Similarly, the study examined that insufficient concentration and focused on deterring the implementation of sustainable value management during the briefing stage. Isa et al, [15] identified the facilities management function, implemented in construction projects. A systematic literature review has been conducted to explore the advantages and constraints of facilities management in value management practices of construction projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…If this matter is considered together with the NGPRS agenda, it is hoped that this distance-based safety analysis model could be adopted in RSI/A and speed management programs so that the NGPRS target could be achieved more quickly and effectively. Another previous study has reported that traffic safety facilities management could be conducted more effectively if facility and value management is integrated at the earlier and/or crucial stages, and as soon as possible (Isa et al, 2017). Moreover, the use of the proposed accident risk analysis model could not only bridge the gap between mobility (time saving, sensation seeking, etc.)…”
Section: Accident Risk Reduction Schemementioning
confidence: 99%